Strategic alliances for value creation - Das, T. K. 1938-; Hitt, Michael A. (Research in strategic alliances., 2012)
Strategic Alliances for Value Creation is a volume in the book series Research in Strategic Alliances that will focus on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series will cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series will also include comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series will seek to disseminate theoretical insights and practical management information that will enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Strategic Alliances for Value Creation contains contributions by leading scholars in the field of strategic alliance research. The 14 chapters in this volume cover a number of significant topics that encompass value creation through strategic alliances in recent times. The chapters cover both the broader topics, such as multi-partner alliances, technology parks, intellectual property rights, knowledge management and culture, portfolio theory, learning in alliances, and open innovation, and the more focused problems of transparency in interfirm accounting, local partner perspective of management control, knowledge in intra-district networks, and alliance partners for entrepreneurial firms. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy areas of research on employing strategic alliances for value creation.